Fungal-mediated synthesis of silver nanoparticles: a novel strategy for plant disease management - Malik, Mansoor Ahmad; Wani, Abdul Hamid; Bhat, Mohd Yaqub; Siddiqui, Sazada; Alamri, Saad A. M.; Alrumman, Sulaiman A. (Frontiers in Microbiology, 2024)
Various traditional management techniques are employed to control plant diseases caused by bacteria and fungi. However, due to their drawbacks and adverse environmental effects, there is a shift towards employing more eco-friendly methods that are less harmful to the environment and human health. The main aim of the study was to biosynthesize silver Nanoparticles (AgNPs) from Rhizoctonia solani and Cladosporium cladosporioides using a green approach and to test the antimycotic activity of these biosynthesized AgNPs against a variety of pathogenic fungi. The characterization of samples was done by using UV-visible spectroscopy, SEM (scanning electron microscopy), FTIR (fourier transmission infrared spectroscopy), and XRD (X-ray diffractometry).During the study, the presence of strong plasmon absorbance bands at 420 nm and 450 nm confirmed the AgNPs biosynthesis by the fungi Rhizoctonia solani and Cladosporium cladosporioides. The biosynthesized AgNPs were 80 to 100 nm in size, asymmetrical in shape and became spherical to sub-spherical when aggregated. Assessment of the antifungal activity of the silver nanoparticles against various plant pathogenic fungi was carried out by agar well diffusion assay. Different concentration of AgNPs, 5 mg/ml 10 mg/ml and 15 mg/ml were tested to know the inhibitory effect of fungal plant pathogens viz. Aspergillus flavus, Penicillium citrinum, Fusarium oxysporum, Fusarium metavorans and Aspergillus aflatoxiformans. However, 15 mg/ml concentration of the AgNPs showed excellent inhibitory activity against all tested fungal pathogens. Thus, the obtained results clearly suggest that silver nanoparticles may have important applications in controlling various plant diseases caused by fungi.